Purulent Pericarditis - Rossell Salinas, Máximo (1992)
13 patients, 5(38,46%) men and 8 (61,53%) women with the diagnosis of Purulent Pericarditis were studied from January 1977 to December 1987. The age varied between 9 months and 43 years old, and 11 (84,61%) were under 16.  The criteria for inclusion were: (1) Suggestive clinical presentation, (2) Electrocardiogram abnormalities, (3) Cardiomegaly on chest X rays, (4) echocardiogram revealing pericardial fluid, (5) bacteriologically proven infection (Blood culture, pericardial fluid and other sources), (6) Septicemia, (7) typical findings on pathologic examination of pericardial tissue, obtained by surgery.  The most frequent clinical symptoms were dyspnea (100%), fever (92,30%), and cough (53,84%). Hepatomegaly (92,30%), pericardial friction rub (76,92%), jugular vein distention (61,53%), were the most frequent signs.  Electrocardiographic features were: Sinus tachycardia 100%, flat T waves 61,53%, low voltaje QRS 46,15%, electrical alternancy 38,46% and ST segment elevation 30,76%. The chest X rays showed cardiomegaly in 92,30, pleural effusion in 61,53% and pneumonia in 53,84% patients. Echocardiography revealed pericardial fluid in all the 7 patients studied.  By pericardiocentesis we obtained pericardial fluid in 13/13; the volume ranged between 5 and 800 ml, median 55ml. The appearance varied from greenish yellow to purulent; the cellularity went from 32 to 198 420/mm3. The average laboratory findings were: polymorphonuclear cells  98,8%, lymphomononuclear cells 10,2%, glucose 68mg%, proteins 5,4g%. The pericardial fluid was cultured in 11/13 and was positive in 6/13 (46,15%). 12/13 patients had blood culture, 8/13 (61,53%) positive.  Bacteriology: Staphylococcus aureus in 6/13 (46,15%), Diplococcus pneumoniae 1/13 (7,69%), Salmonella typhi 1/13 (7,69%). In 5/13 (38,46%) patients nosocomial Gram negative infection occurred, due to Salmonella sp, Escherichia coli, Klebsiella and Pseudomonas. In 2/13 (15,38%) more than one superinfecting bacterial species was found.  Associated illnesses: pleural empyema 8/13 (61,53%), pneumonia 7/13 (53,84%), infectious arthritis in 5/13 (38,46%) and osteomyelitis in 4/13 (30,76%). Sepsis was considered in 8/13 (61,53%) patients. Treatment: Antibiotics plus pericardiocentesis in 3/13 (23,07%); antibiotics pericardiocentesis and surgery in 10/13 (76,92%). Lethality was 5/13 (38,46%) patients.  Early suspicion, clinical thoroughness, the use of electrocardiography, chest X rays, echocardiography, pericardiocentesis and opportune pericardiectomy has changed the natural history of the disease, from 100% lethality before the antibiotic era to 23,22%, in most of the reports in the 80's, with new diagnostic and therapeutic tools and trends.